Estrategia comunicacional para la venta de los departamentos de la Villa del Atleta - Oblitas Toro, Camila (2019)
In this work, the communication proposal will be developed to inform about the Villa del Atleta and Mi Vivienda Verde credit. The main objective is to achieve the transaction, completing the sale of 100% of the departments. Villa del Atleta, an important legacy of the Lima 2019 Pan American and Parapanamerican Games, is a space created with the perspective of environmental sustainability, promotion of sports and inclusion of disabled people. Located in Villa El Salvador, it is an ideal home for small families of sectors C and D.